Выль бугро мон ӵупи: кылбуръёс / Анатолий Комаров - Комаров Анатолий Ермолаевич (Удмуртия, 1981)
Экземпляры: ф. 2 (20220401) / Инвентарный номер: 2179 / Цена: 0.20 / Авт.знак: К 63 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)